2014
DOI: 10.1103/physreve.89.052809
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive evolution of experimental braided rivers

Abstract: Water flowing over a loose granular bed organizes into a braided river, a network of ephemeral and interacting channels. The temporal and spatial evolution of this network of braided channels is not yet quantitatively understood. In ∼1 m-scale experiments, we found that individual channels exhibit a self-similar geometry and near-threshold transport conditions. Measurements of the rate of growth of topographic correlation length scales, the time scale of system-slope establishment, and the random spatial decor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 41 publications
6
36
0
Order By: Relevance
“…Parker's model (Parker (1978a)) predicted τ * bf /τ * c ≈ 1.2 for equilibrium bed-load rivers, in agreement with observations of natural gravel-bed rivers (Paola et al (1992); Parker et al (1998); Dade and Friend (1998);Parker et al (2007); Phillips and Jerolmack (2016)) and laboratory experiments (Ikeda et al (1988); Pitlick et al (2013); Reitz et al (2014)). In terms of the regime equations 1, gravel-bed rivers thus follow expectations from the threshold theory but with a slight offset due to their higher bankfull Shields stress (Métivier et al (2017)).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Parker's model (Parker (1978a)) predicted τ * bf /τ * c ≈ 1.2 for equilibrium bed-load rivers, in agreement with observations of natural gravel-bed rivers (Paola et al (1992); Parker et al (1998); Dade and Friend (1998);Parker et al (2007); Phillips and Jerolmack (2016)) and laboratory experiments (Ikeda et al (1988); Pitlick et al (2013); Reitz et al (2014)). In terms of the regime equations 1, gravel-bed rivers thus follow expectations from the threshold theory but with a slight offset due to their higher bankfull Shields stress (Métivier et al (2017)).…”
supporting
confidence: 82%
“…Channels formed by seepage erosion in sand (Devauchelle et al (2011)) are observed to transport sand as bedload and, like gravel bedload rivers, cluster approximately at the threshold of motion. Similarly, sand-bedded rivers in laboratory experiments also form near-threshold channels (Reitz et al (2014); Métivier et al (2016);Federici and Paola (2003)). …”
mentioning
confidence: 80%
“…In sand-bed rivers, the geometry of braided threads appears to be indistinguishable from that of meandering ones. This observation accords with recent laboratory experiments Reitz et al, 2014). To our knowledge, this similarity has not been fully investigated in gravel-bed rivers.…”
supporting
confidence: 78%
“…If confirmed, this would suggest that a braid results from the collective behavior of individual threads, the property and dynamics of which would be close to that of meandering threads (Sinha and Friend, 1994;Ashmore, 2013;Reitz et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is thus reasonable to assume that the deposit inherits the slope of the channels that built it. The way a river selects its morphology is still a matter of debate, but it has been recently pointed out that most laboratory rivers, including those flowing over an experimental fan, remain near the threshold for sediment transport (Reitz and Jerolmack, 2012;Seizilles et al, 2013;Reitz et al, 2014;Métivier et al, 2017). Assuming a channel is exactly at threshold yields a theoretical relationship between its water discharge and its slope (Glover and Florey, 1951;Hen- derson, 1961).…”
Section: Mass Balancementioning
confidence: 99%